Meningkatkan Hasil Belajar Matematika Melalui Pembelajaran Berdiferensiasi dengan Model Problem Based Learning - Arisandi, Ovrina Resti (Jurnal Didaktika Pendidikan Dasar, 2024)
This study aims to improve student learning outcomes in Mathematics subject through differentiated learning with Problem Based Learning (PBL) models. The approach used in this study was qualitative with the Classroom Action Research (PTK) method which was carried out in two cycles, which went through the stages of planning, implementing and reflecting for each cycle. Data collection instruments were obtained through observation sheets and test sheets. Data on student learning test results for each cycle were analyzed using the formula for average scores and percentages of classical learning completeness, while data from observations of student activity were analyzed using the average score for each criterion. The results showed an increase in student activity in the first cycle an average of 75% and an average of 92.5% in the second cycle. Furthermore, in the student learning outcomes test there was also an increase from cycle I obtained 76.92% to 92.3% in cycle II. Based on this research, it can be concluded that there is an increase in Mathematics learning outcomes through differentiated learning with Problem Based Learning (PBL) models.